BERBAGAI FORMULASI KEBUTUHAN NUTRISI PADA SISTEM HIDROPONIK - -, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2008)
ABSTRACT Hydroponics is the cultivation system with growing media other than soil like gravel. sand, charcoal, charcoal husk, broken bricks and others. Hydroponic systems all nutritional needs made ​​available in the right quantity and concentration of plant growth and development so that we can be cultivated to grow and develop properly. Nutrition administered through the media in different ways, there are watered by the media, flow, drip systems and others. Many formulas that can be used in plant cultivation system hidoponik namely: netherland standard formula, formula kuwait, Bengal formula, formula florida and finished materials. For starters it is a formula that has been so highly recommended because it is uncomplicated and easy to apply. Key word : nutritional formulation hydroponic system